The Effect of Service Quality and Product Facilities on Consumer Satisfaction with Prices (Toll Free) as Intervening Variables (Case Study on Jasa Marga Mabar 1 Toll Gate) - Berupilihen br Ginting; Purjianto; Ahmad Fadli; Ahmad Rivai; Fichri Alfisyahri (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of service quality and product facilities on consumer satisfaction with tariffs (toll fees) as an intervening variable (Case Study on Jasa Marga Mabar 1 Toll Gate). This type of research is quantitative research. The population in this study is 118 thousand vehicles and the total sample is 100 toll net users. The data analysis technique in this study used multiple regression data analysis and hypothesis testing. The results of this study are the quality of service has a positive and significant effect on toll rates at the Mabar toll gate 1. Service quality has a positive and significant effect on consumer satisfaction at the Mabar toll gate 1. Product facilities have a positive and significant effect on toll rates at the Mabar toll gate 1. Facilities product has a positive and significant effect on consumer satisfaction at the Mabar toll gate 1. Toll tariffs have a positive and significant effect on consumer satisfaction at the Mabar toll gate 1. Service quality has a positive and significant effect on customer satisfaction through toll rates at the Mabar toll gate 1 Product facilities have a positive effect and significant to customer satisfaction through toll rates